Análise termodinâmica de reações de reforma autotérmica via método de maximização de entropia - Souza, Thiago Leandro de (2015)
There are many studies in the literature that propose to perform a thermodynamic analysis of autothermal reforming reactions. Most of them use the Gibbs free energy minimization. This method does not meet directly the thermalneutral condition of autothermal reactions, limiting operational conditions evaluated in these analyzes. In this work are presented thermodynamic analyzes of different reaction autothermal systems through the simultaneous calculation of chemical and phase equilibrium by using the entropy maximization method - which directly meet the thermalneutral condition. First, a thermodynamic analysis of methane autothermal reforming was performed using the ideal gas model to simulate the gas phase behavior. In this analysis, it were investigated the effects of pressure, initial temperature and composition at the equilibrium composition and temperature of the reaction system. It were also determined the optimum conditions to maximize hydrogen production the feasible conditions for synthesis gas production. The solution of the nonlinear programming problem, generated from the thermodynamic model obtained, was conducted through CONPT2 solver, based on the Generalized Reduced Gradient algorithm (GRG), present in GAMS 21.6 software. Further, it was performed a convexity analysis of entropy maximization method used for the ideal gas model, which demonstrated the uncertainty of the convexity model implemented at the entropy maximization method employee. It was Implemented the particle swarm algorithm (EP) for the proposed method for verification of the optimum points calculated by GRG algorithm. The results of the use of EP proposed for the autothermal reforming of methane are presented and compared with those obtained by the GRG algorithm. In another step, it was performed a thermodynamic analysis of different autothermal reforming reactions (autothermal reforming, dry autothermal reforming, and autothermal reforming with supercritical water) applied to different substrates (ethanol, glycerin and glucose), using the equation of state of Peng-Robinson to predict the gas phase behavior. It were investigated the effects of process variables, temperature and initial composition on the equilibrium composition and temperature at equilibrium conditions of these reactive systems. A comparison between each technologies considered for each substrate shown that the autothermal reforming using supercritical water and autothermal reforming reactions allow an increased production of hydrogen, while dry autothermal reforming and autothermal reforming reactions are more favorable for the production of synthesis gas. The proposed methodology has proven to be the most suitable for the thermodynamic analysis in adiabatic reactions, it allows obtaining direct thermoneutral condition and the prediction of the final temperature of the process and may be useful in the development and optimization of processes occurring in adiabatic condition, as in the case of autotérmicas reforming reactions studied in this work.